Duodenal Villous Atrophy in a TTG-Negative Patient Taking Olmesartan: A Case Report and Review of the Literature. (14th April 2016) - Kulai, Tasha; Arnason, Thomas; MacIntosh, Donald; Igoe, John
Abstract : Olmesartan, an angiotensin II receptor antagonist used to treat hypertension, is associated with few adverse effects. Here, a case of severe sprue-like enteropathy and acute kidney injury is described in a 68-year-old male taking olmesartan for 3-4 years. He presented to hospital with a five-week history of diarrhea, vomiting, and a 20 lb weight loss. Anti-TTG was negative with a normal IgA. Biopsies of the distal duodenum and duodenal cap revealed marked blunting of the villi with near complete villous atrophy of the biopsies from the bulb. There was an increase in intraepithelial lymphocytes as well as neutrophils in the surface epithelium. The patient's diarrhea improved upon discontinuation of olmesartan and he returned to his previous weight. Repeat endoscopy four months later demonstrated complete resolution of inflammatory change with normal villous architecture. Long-term olmesartan use is associated with severe sprue-like enteropathy. The mechanism of intestinal injury is unknown. Duodenal biopsy results may mimic other enteropathies such as celiac disease. Physicians should consider medications as potential etiologies of enteropathy.